Service Recovery Evaluations in Online Travel Platforms: Evidence from Indian Hospitality Industry (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Although considerable research attention has  been given to the domain of online service failure  and recovery in the recent years, extant literature  has been inconclusive on the relative impact  of each dimension of justice on post recovery  customer outcomes following a successful service  recovery. Hence this study examines the impact  of online service recovery on post recovery  customer outcomes as a result of varying justice  dimensions such as distributional, procedural  and interactional. A scenario-based role-playing  survey was done among 325 Indian online  hospitality customers in and results from a  structural equation modelling revealed that  distributive justice had the highest impact  among the three dimensions of justice. The study  provides significant contribution to both theory  and practice which helps the managers to design  robust strategies for addressing service failures in  a hospitality context.
Keywords: online service failure; online service recovery; justice perceptions; distributive justice; online hospitality